Payroll Accounting Information System Analysis at Sugarcane Plantation Company Wahyu Daya Sejahtera Ltd - Ursulah Diana Fitriani (NAROTAMA UNIVERSITY, Indonesia, 2022)
Wahyu Daya Sejahtera Ltd is one of the companies engaged in sugarcane farming that has problems in payroll. What often happens in salary management is the calculation of working days, and salary deductions or salary payments that are less precise because the information obtained is inaccurate. This study aims to determine how the application of payroll accounting information systems. In this study, the method used is descriptive analysis method with a qualitative approach and the data collection techniques used are primary and secondary collected by means of interviews, observation and documentation, and the technique used is data analysis. The results obtained from this study are the application of payroll accounting information systems at Wahyu Daya Sejahtera Ltd has not yet fully implemented the payroll system in accordance with the description of Mulyadi's payroll accounting information system, because there are still indicators of payroll procedures that the company has not implemented optimally. The advice given to PT. Wahyu Daya Sejahtera, the company must add SOP for the parts involved in the payroll system so that there is no overlap in the implementation of tasks in carrying out operational tasks, Wahyu Daya Sejahtera Ltd is expected to be able to take advantage of existing technology, and increase the number of employees, especially in the finance department so that functions can work effectively.